Marketing management and the impact of social marketing on the Iraqi market - Muter, Marwan Abdulrazak (Eximia, 2023)
While the number of people using social media continues to rise, there is surprisingly little academic study that examines the possibilities marketing’s use of social media in terms of both communication and promotion. This article presents the findings of a pilot research that surveyed 150 students at a major university in Iraq to investigate the potential impact of social media on the purchase decisions of young people. It was discovered that the respondents (young people) had a good understanding of computers and use social media sites, which boosts their value as clients. These young people are also increasingly avoiding traditional forms of advertising in favour of social media, and they frequently make purchases based on information gleaned from these sites because they find it to be sufficient for making decisions, reliable, convenient, and wasting less of their time. Marketers aiming their products towards the young market may want to take the results into account when formulating marketing and public relations plans.